Observational study of segmental epidural anesthesia for orthopedic surgeries - Badheka, Jigisha; Dalvani, Khatija; Singh, Aditya; Gohil , Yagnesh (International Journal of Research in Medical Sciences, 2023)
Background: Epidural anaesthesia is suitable technique for lower abdominal and lower limb surgery. Compared to conventional epidural anesthesia (EA), segmental epidural anaesthesia (SEA) denotes the use of a small volume enough to block only the segments involved in the field with stable hemodynamics and limited spread of analgesia. We decided to do study of SEA for lower limb surgeries. Aim was to observe characteristic of sensory and motor block, quality of analgesia, hemodynamics and peri-operative complications. Methods: After institutional ethical committee approval, prospective observational study of SEA for orthopedic surgeries was carried out in 130 patients of 18 to 60 years of either sex with ASA grade І-Ш. For SEA, we used bolus dose of lignocaine with adrenaline (L+A) 2% 8 to 12 ml injected over 4 minutes according to anticipated segments required to be blocked and patient’s condition and type of surgery. Top up dosages were repeated every 60 minutes. Quality of analgesia and block, total local anesthetic used and hemodynamics were recorded intraoperatively. Results were analysed statistically and were compared using the student’s paired ‘t’ test. P value <0.05 was considered as significant. Results: Requirement of bolus dose was 8 ml, 10 ml and 12 ml in 78 patients, 31 patients and 7 patients respectively. In all patients 1st top up dose was given while 2nd top up was required in 32 patients only. Intra op MAP remains near to baseline. Quality of block was excellent in 66 patients (55%), good in 35 patients (29%) and fair in 15 patients (12.5%). Conclusions: We concluded that SEA is a safe and reliable technique for orthopedic surgeries with stable hemodynamics, limited spread of analgesia involving only required segments with minimal side effects.